Proses Berpikir Matematis Siswa dalam Menyelesaikan Masalah Matematika di tinjau dari Tipe Kepribadian Keirsey - Hamidah, Khusnul; Suherman, Suherman (Al-Jabar: Jurnal Pendidikan Matematika, 2016)
This study aims to describe the process of mathematical thinking of students in solving mathematical problems in terms of Keirsey's personality type. This research is a qualitative-descriptive research. Research subjects taken are MAN 2 Tulang Bawang Barat class XI students by purposive sampling. Research subjects amounted to 2 people from each personality type. Data collection is done by observation, interview, and documentation. Data validity using technique triangulation. Data analysis techniques used are the concept of Miles and Huberman, namely data reduction, data presentation, and conclusion. The results showed that each of Keirsey's students in solving mathematical problems was more likely to be a student of a Guardian personality type. In solving mathematical problems begins with the acceptance of information marked by understanding the problem involves knowing what is known (M1), knowing what is being asked (M2), knowing the required requirements in problem solving (M3), as well as making the model of math from the problem with its own understanding (M4). Then proceed with the processing of information marked by implementing the problem-solving plan (R1) and proceed with executing the plan to get the answer (P1), but the steps are not complete. While in rechecking the answer (C1) students do re-check, then in drawing a conclusion (C2), students draw conclusions only on some tests.